2015
DOI: 10.5194/nhessd-3-2119-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assess arsenic distribution in groundwater applying GIS in capital of Punjab, Pakistan

Abstract: Abstract. Arsenic contamination of groundwater resources threatens the health of millions of people worldwide, particularly in the densely populated river deltas of Southeast Asia. Arsenic causes health concerns due to its significant toxicity and worldwide presence in portable water. The major sources of arsenic pollution may be natural process such as dissolution of arsenic containing minerals and anthropogenic activities. Lahore is groundwater dependent city, arsenic contamination is a major issue of portab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
(31 reference statements)
1
9
0
Order By: Relevance
“…The lowest water quality observed in shallow aquifers was attributed to SW, urban water and sanitation systems, high urban density, poor solid waste disposal, and agricultural activities, while the high arsenic levels in deep aquifers was related to the high pumping rates for different sectors, such as the urban and industrial sectors (Farooqi et al, 2003). Various studies on different water supply sources have concluded that deep aquifers can be protected against arsenic percolation by shallow pumping (Hossain and Piantanakulchai, 2013;Akhtar et al, 2015). Our findings show that GW overexploitation results in higher arsenic concentrations owing to contaminated recharge, while the high arsenic concentrations in deep GW may be from high pumping rates over the years.…”
Section: High Equal Frequency Factors In Water Bodiesmentioning
confidence: 56%
“…The lowest water quality observed in shallow aquifers was attributed to SW, urban water and sanitation systems, high urban density, poor solid waste disposal, and agricultural activities, while the high arsenic levels in deep aquifers was related to the high pumping rates for different sectors, such as the urban and industrial sectors (Farooqi et al, 2003). Various studies on different water supply sources have concluded that deep aquifers can be protected against arsenic percolation by shallow pumping (Hossain and Piantanakulchai, 2013;Akhtar et al, 2015). Our findings show that GW overexploitation results in higher arsenic concentrations owing to contaminated recharge, while the high arsenic concentrations in deep GW may be from high pumping rates over the years.…”
Section: High Equal Frequency Factors In Water Bodiesmentioning
confidence: 56%
“…Economic development pressures have accelerated human activities to rise in production (industrial as well as agricultural) and urbanization is a major source of surface water pollution in the Dongting plan. BI observed that in China, domestic sewage has polluted lakes (Akhtar et al, 2015;Bi et al, 2018), while another researcher identified agricultural activities caused by watersheds (Gao and Mucci, 2003). Similarly, due to untreated industrial effluents and wastes, various pollutants values in river waters did not meet standards.…”
Section: Resultsmentioning
confidence: 99%
“…More seriously, the over-abstraction of groundwater has led to increased contamination of the aquifer, with a higher-than-acceptable concentration of arsenic and a looming threat of saline water intrusion from Raiwind area towards the fresh groundwater in Lahore [47]. The Pakistan Council of Research in Water Resources (PCRWR) conducted a study to assess arsenic in Lahore City in 2009 and found that most groundwater samples had a concentration higher than 50 µg/L [48]. In addition, the cost of electricity to produce water has increased by 110.9% (Figure 9).…”
Section: Factors Influencing Water Demandmentioning
confidence: 99%